Joyful noise - Nathanson, Michael (Michael G.); Graff, Todd.; Latifah, Queen; Parton, Dolly; Palmer, Keke.; Vance, Courtney B.; Jordan, Jeremy, 1973-; Kristofferson, Kris.; Alcon Entertainment (Firm); Farrell Paura Productions (Firm); O. N. C. Entertainment (Firm); Warner Home Video (Firm) (Burbank, CA : Distributed by Warner Home Video, 2012)
The small town of Pacashau, Georgia, has fallen on hard times, but the people are counting on the church choir to lift their spirits by winning the national Joyful Noise Competition. But the discord between its two leading ladies threatens to tear everything apart.
DVD, region 1, widescreen presentation; Dolby digital 5.1 surround; dual layer.
In English or dubbed Spanish; optional subtitles in French or Spanish; English subtitles for the deaf and hard of hearing.
Queen Latifah, Dolly Parton, Keke Palmer, Courtney B. Vance, Jeremy Jordan, Kris Kristofferson.
Music, Mervyn Warren ; editor, Kathryn Himoff ; director of photography, David Boyd.
MPAA rating: PG-13; for some language including a sexual reference.
Special features: Make some noise featurette ; Leading ladies featurette.
Keywords: Choirs (Music) -- Georgia -- Drama; Conflict of generations -- Drama; Small cities -- Georgia -- Finance -- Drama; Coros (Música) -- Georga -- Teatro; Conflicto entre generaciones -- Teatro; Feature films; Comedy films; Musical films; Video recordings for the hearing impaired; Feature films; Comedy films